Traditional Market Development Study Based Local Wisdom in Indonesia - Siswanto, Rudi (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This study aims to identify the traditional market development strategy based on local wisdom in Koto Baru Traditional Market, X Koto Subdistrict, TanahDatar District. This research is a qualitative research, and is conducted in Koto Baru Traditional Market of X Koto Subdistrict of Tanah Datar Regency which is taken based on Purposive Sampling. The data in this research is collected through observation, interview and documentation and continued with data analysis, Interpretation and Withdrawal Conclusion and then continued to do SWOT analysis to get the strategy in development of Traditional Market of KoToBaru Sub X Koto Tanah Datar regency. The results show Based on the results and discussion above it can be concluded that the study of market development based on the arrangement and management of traditional markets in Traditional markets District X Koto Flat district is the Government together with the community together develop the market as an agricultural production market organic farming, Government and society jointly promote the market, Make improvements and additions to various facilities and infrastructure Traditional Market, Providing an understanding to the public the importance of maintaining and protecting Traditional Markets, Focusing on improving the infrastructure of market stalls so as not to disturb the pedestrians, Doing Market development by not damaging the environment Market, economic activities of the community by providing capital in developing organic agricultural markets, Improving the relationship of cooperation between the community and government in market development., Keeping peace and security n market. In the execution of its management has formed a form of market as the transfer of the market for the conditions that should be controlled in market management, but the new problem is the people who carry out market activities are reluctant to move to the place that has been provided